2018
DOI: 10.1088/1361-6544/aa9462
|View full text |Cite
|
Sign up to set email alerts
|

Small scale exact coherent structures at large Reynolds numbers in plane Couette flow

Abstract: Abstract. The transition to turbulence in plane Couette flow and several other shear flows is connected with saddle node bifurcations in which fully 3-d, nonlinear solutions, so-called exact coherent states (ECS), to the Navier-Stokes equation appear. As the Reynolds number increases, the states undergo secondary bifurcations and their timeevolution becomes increasingly more complex. Their spatial complexity, in contrast, remains limited so that these states cannot contribute to the spatial complexity and casc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…At large Reynolds number, the nonlinear self-interaction of the Rayleigh mode is confined to a critical layer where the ECS phase speed matches the streak velocity. Blackburn, Hall & Sherwin (2013) and Eckhardt & Zammert (2018) have demonstrated that VWI states can exist on ever smaller spatial scales as the Reynolds number is increased. Specifically, when the streamwise and spanwise wavenumbers are increased such that their ratio remains fixed, the ECS adopt a self-similar form in which the coherent structure becomes localized in the wall-normal direction within a 'production' layer having a thickness comparable to the inverse spanwise (or streamwise) wavenumber.…”
Section: Introductionmentioning
confidence: 99%
“…At large Reynolds number, the nonlinear self-interaction of the Rayleigh mode is confined to a critical layer where the ECS phase speed matches the streak velocity. Blackburn, Hall & Sherwin (2013) and Eckhardt & Zammert (2018) have demonstrated that VWI states can exist on ever smaller spatial scales as the Reynolds number is increased. Specifically, when the streamwise and spanwise wavenumbers are increased such that their ratio remains fixed, the ECS adopt a self-similar form in which the coherent structure becomes localized in the wall-normal direction within a 'production' layer having a thickness comparable to the inverse spanwise (or streamwise) wavenumber.…”
Section: Introductionmentioning
confidence: 99%
“…The stability boundary of the laminar flow, which separates initial conditions that relaminarise from those that become fully turbulent, is referred to as the edge (Skufca et al 2006;Schneider et al 2008Schneider et al , 2007 and plays a fundamental role in structuring the state space of turbulence. The computation of invariant solutions of the Navier-Stokes equations has allowed for a simplified analysis of a number of physical processes, including an equilibrium selfsustaining process (Waleffe 1998), the self-similarity of equilibria localised in the wallnormal direction (Eckhardt & Zammert 2018) and the high-Re inner-scaling of wallattached equilibria (Yang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The value of the Couette control parameter Re P CF formally depends on the arbitrarily chosen H + reflecting the fact that a solution localised at the wall, only depends on the shear rate at the wall while the distance of the second upper wall and thereby the value of Re P CF is irrelevant. Thus, at asymptotically high Re, all state space structures representing wall attached flow fields in the MFU of ASBL have counterparts in high Reynolds number PCF, such as those identified by Eckhardt & Zammert (2018). This suggests that the relevant statespace structures for near-wall turbulence that we identified in ASBL are universal in that they are not only independent of Re when expressed in inner units but also do not depend on the specific shear flow system considered.…”
Section: Invariant Solutions In the Minimal Flow Unitmentioning
confidence: 60%
“…Deguchi (2015) identifies a solution which scales in inner units at high Reynolds numbers but is not localised at the wall. More recently Eckhardt & Zammert (2018) present two solutions in plane Couette flow, one localized in the center of the channel and one attached to the wall. The solutions are followed up to a Couette Reynolds number of Re = 100, 000, and become approximately Reynolds number independent when rescaled by the inner length scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation